A moderated mediation analysis on the relationship between metacognition and mathematical resilience of gifted students - Turgut, Sedat; Uğurlu, Mahir; Turgut, Sedat; Uğurlu, Mahir (Wiley, 2024)
This study examined the mediator role of mathematics motivation and the moderator role of mathematics anxiety (MA) in the relationship between metacognition (MC) and mathematical resilience (MR). The participants are 202 gifted students. Data were collected through the Metacognitive Awareness Scale, MR Scale, Revised MA Rating Scale, and Mathematics Motivation Scale. Regression analysis based on the bootstrap technique was used to test the hypothetical model, including mediation, moderation, and moderated mediation relations. The study results showed that MC indirectly positively affects MR through mathematical motivation. MA has a moderator effect on the positive effect of mathematics motivation on MR. The positive effect of mathematics motivation on MR decreases as MA increases. MA has a moderating effect on the indirect effect of MC on MR through mathematics motivation. The positive effect of MC on MR decreases as math anxiety increases. Metacognition (MC) indirectly positively affects mathematical resilience (MR) through mathematical motivation.Mathematics anxiety (MA) moderates the positive effect of mathematics motivation on MR.MA moderates the indirect effect of MC on MR through mathematics motivation.
Keywords: Gifted Students; Mathematical Resilience; Mathematics Anxiety; Mathematics Motivation; Metacognition